If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11x+3=8x+7x
We move all terms to the left:
11x+3-(8x+7x)=0
We add all the numbers together, and all the variables
11x-(+15x)+3=0
We get rid of parentheses
11x-15x+3=0
We add all the numbers together, and all the variables
-4x+3=0
We move all terms containing x to the left, all other terms to the right
-4x=-3
x=-3/-4
x=3/4
| 5y=3y+3 | | 11÷4x+9=3 | | x²+4x-96=0 | | 12(12x+4)=144 | | 39=3x-6. | | 2,8-4x=0 | | 6x=2x= | | 3(x=2)=9 | | 2b/3-4=6 | | x5x=−9 | | 2x16=x+20 | | 2x-3=6x+5. | | 5x2+100=60x | | 12+9h=52 | | 12y-8=136 | | 7y+5=4 | | 9x-3=5x+19 | | 4x=36-x | | 9x+15=13x+27 | | 5y-35=3y | | 0.12n+0.5=0.7 | | 4.5+0,1x=2.4+0.4x | | 0.75+0,1x=2.4+0.4x | | 4(2y-5)=2(y+14) | | 0.5/1.5=x/0.25 | | 5(2x–7)=103 | | 0.75+0,1x=0.3+0.4x | | 8a+9=48 | | 2x+9=-7; | | 5x−1/5x+6=2/3 | | 1+0.75x=4+0.4x | | 1+0.9x=8+0.8x |